Relation of Timing of Percutaneous Coronary Intervention on Outcomes in Patients With Non-ST Segment Elevation Myocardial Infarction - Batchelor, R.J.; Dinh, D.; Brennan, A.; Wong, N.; Lefkovits, J.; Reid, Christopher; Duffy, S.J.; Chan, W.; Cox, N.; Liew, D.; Stub, D. (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2020)
International guidelines suggest revascularization within 24 hours in non-ST segment elevation myocardial infarction (NSTEMI). Within a large population cohort study, we aimed to explore clinical practice regarding timing targets for percutaneous coronary intervention (PCI) in NSTEMI. The Victorian Cardiac Outcomes Registry was established in 2013 as a state-wide clinical quality registry, pooling data from public and private PCI capable centers. Data were collected on 11,852 PCIs performed for NSTEMI from 2014 to 2018. Patients were divided into 3 groups by time of symptom onset to PCI (<24 hours; 24 to 72 hours; >72 hours). We performed multivariable logistic regression analysis conditional on several baseline covariates in investigating the impact of timing of PCI in NSTEMI on clinical outcomes. Patients who underwent PCI within 24 hours represented 18.4% (n = 2,178); 24 to 72 hours 45.8% (n = 5,434); >72 hours 35.8% (n = 4,240). Patients waiting longer for PCI were older (62.6 ± 12.2 vs 64.8 ± 12.6 vs 67.0 ± 12.7, p <0.001), more likely to be female (23.1% vs 24.2% vs 26.4%, p = 0.007), and have diabetes (18.6% vs 21.1% vs 27.1%, p <0.001). Multivariate logistic regression found that as compared with PCI <24 hours, PCI 24 to 72 hours and PCI >72 hours of symptom onset were associated with a decreased risk of 30-day mortality (odds ratio 0.55; 95% confidence interval 0.35 to 0.86, p = 0.008 and odds ratio 0.64; 95% confidence interval 0.35 to 1.01, p = 0.053, respectively). There was no significant difference in 30-day mortality between groups following exclusion of patients presenting with cardiogenic shock or out of hospital cardiac arrest requiring intubation. In conclusion, many registry patients undergo PCI outside the 24-hour window following NSTEMI. This delay is at odds with current guideline recommendations but does not appear to be associated with an increased mortality risk.